ESTRANHOS NO NINHO? PROFESSORES HOMENS NA EDUCAÇÃO INFANTIL DE CAMPINAS–SP - Cíntia De Paula Borges Menezes (2023)
This research focuses on cisgender male teachers who work in Early Childhood Education, a profession considered feminine and occupied mostly by female teachers. The research is located in the field of gender studies and Education and aims to understand and analyze the challenges experienced by teachers when their adult male bodies enter daycare and preschool. Theoretical references will be: Bento (2011), Louro (1997; 2000; 2010), Monteiro (2014), Ramos (2011), Rosemberg (1996), Sayão (2005), Scott (1990), among other authors . This is a qualitative study, which used several data collection instruments, namely: semi-structured interview; open questionnaire; immersion in everyday school life (ethnographic type); and field diary. The research was carried out with 21 (twenty-one) male teachers who work in daycare centers and preschools in the municipal network of Campinas–SP and 31 (thirty-one) people from the school community who interact with them. The analysis found that the work of these professionals is inevitably crossed by the issue of gender, especially the notion of hegemonic masculinity. The presence of these male teachers in Early Childhood Education not only changes the expected landscape, but also raises suspicion, distrust, estrangement and, occasionally, attempts to segregate that space. The questions, trajectory and findings of this research highlight the pressing need to break with hegemonic paradigms and discuss gender stereotypes in the educational context. Keywords: Early Childhood Education; male teachers; gender; masculinities.